Implementation of the configuration structure of an integrated computational core of a pulsed NQR sensor based on FPGA - Samila, Andriy; Hotra, Oleksandra; Majewski, Jacek (MDPI, 2021)
This paper presents a method for implementing the configuration structure of an integrated computational core of a pulsed nuclear quadrupole resonance (NQR) sensor based on a field-programmable gate array (FPGA), which comprises the following modules: a three-channel direct digital synthesizer (DDS), a pulse sequence shaper and a software-defined radio. Experimental studies carried out using the in-circuit analyzer SignalTap Logic Analyzer have confirmed the reliability of the correct and stable operation of the functional modules of the configuration structure at all stages of signal transformations, starting from the formation of the envelope of the excitation pulses and ending with the obtainment of low-frequency quadrature signals at the outlet of the compensating filters. The time and frequency dependences of the amplitude of the output signals generated using the DDS based on a 48 bit phase accumulator are investigated. This development can be used when creating pulsed coherent NQR sensors in the frequency range of 1 MHz–50 MHz.
Keywords: digital filter; digital down conversion; direct digital synthesis; FPGA; nuclear quadrupole resonance; phase accumulator; sensor; software-defined radio